Nimble Cloning: A Simple, Versatile, and Efficient System for Standardized Molecular Cloning - Yan, Pu; Zeng, Yanjing; Shen, Wentao; Tuo, Decai; Li, Xiaoying; Zhou, Peng (Frontiers in Bioengineering and Biotechnology, 2020)
Molecular cloning is one of the most fundamental technologies in molecular biology, and has been critical for driving biotechnological advances. In this study, we developed a novel method, Nimble Cloning, for standardized cloning. Nimble Cloning uses SfiI and T5 exonuclease to linearize the vector and generate 3′-overhangs simultaneously. All of the Nimble Cloning destination vectors contain unique nucleotide sequences and SfiI recognition sites for standardized cloning. Both PCR products and entry clones can be used for the cloning reaction in the Nimble Cloning system. The unique nucleotide sequences were associated with efficient cloning, were suitable for gene expression in both prokaryotic and eukaryotic expression systems, and enabled the reuse of the DNA fragments or entry clones. Nimble Cloning is applicable for the cloning of single or multiple fragments as well as for the cloning at multiple sites. This novel method is simple, versatile, and efficient, and may be useful for the standardized molecular cloning required for diverse applications. It may also facilitate modular DNA assembly and multi-level construct assembly because it can use the entry clone directly.